The Influence Of Financial Performance And Tax Avoidance On Company Value (An Empirical Study Of Food And Beverage Companies Listed On The Indonesia Stock Exchange For The Period 2020-2024) - Setiawan, Hendra; Junaidi, Ahmat; Ranidiah, Furqonti (UNIVED Press, 2026)
This study aims to determine whether return on assets (ROA), debt to equity ratio (DER), and tax avoidance (ETR) influence company value. The research was conducted on food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. This study employed purposive sampling and statistical analysis, including classical assumption tests, using IBM SPSS Statistics version 22. The sample consisted of 21 food and beverage companies listed on the IDX. Thus, the total number of companies was 21 multiplied by 5 years, resulting in 105 observations. The results of this study indicate that: Financial performance proxied by return on assets (ROA) influences company value with a sig value of 0.000. Financial performance proxied by debt to equity ratio (DER) influences company value with a sig value of 0.000. Tax avoidance (ETR) does not affect company value with a significance level of 0.566. Return on assets (ROA), debt-to-equity ratio (DER), and tax avoidance (ETR) simultaneously affect company value with a significance level of 0.00